1983
DOI: 10.1017/s0043174500069150
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of 2,4-DB, Acifluorfen, and Toxaphene Applied to Foliage of Sicklepod (Cassia obtusifolia)

Abstract: The dimethylamine salt of 2,4-DB [4-(2,4-dichlorophenoxy)butyric acid] combined with toxaphene (chlorinated camphene) or acifluorfen [5-(2-chloro-4-(trifluoromethyl)phenoxy)-2-nitrobenzoic acid] and toxaphene combined with acifluorfen at several rates each were applied in the greenhouse and field to sicklepod (Cassia obtusifoliaL.) to determine interactions. Toxaphene plus 2,4-DB treatments produced synergistic or additive responses in the greenhouse and in the field. Antagonistic or additive responses were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Chlorimuron was more active on common cocklebur, sicklepod, and morningglory while metribuzin was more active on hemp sesbania and prickly sida. At rates where both herbicides were partially active, the interaction of metribuzin and chlorimuron was quantified with EF values from 0.6 to 2.6 and mix ture responses near what would be expected with Colby's equation (6,15). In these cases, the inter action allowed for lower rates in mixture than if either herbicide was used alone.…”
Section: Resultsmentioning
confidence: 92%
“…Chlorimuron was more active on common cocklebur, sicklepod, and morningglory while metribuzin was more active on hemp sesbania and prickly sida. At rates where both herbicides were partially active, the interaction of metribuzin and chlorimuron was quantified with EF values from 0.6 to 2.6 and mix ture responses near what would be expected with Colby's equation (6,15). In these cases, the inter action allowed for lower rates in mixture than if either herbicide was used alone.…”
Section: Resultsmentioning
confidence: 92%
“…To reduce interference from other weeds in all studies, herbicides that had very little or no effect on sicklepod were used across all studies when needed (Richburg et al 1993;Waldrop and Banks 1983;Wehtje et al 1992;Wilcut et al 1997). Bentazon at 0.56 or 0.84 kg ai/ha, acifluorfen at 0.24 or 0.42 kg ai/ha, and fomesafen at 0.39 kg ai/ha were used to suppress morningglory species (Ipomoea lacunosa L., and I. hederacea var.…”
Section: Methodsmentioning
confidence: 99%
“…when applied with imidacloprid. Alternatively, Waldrop and Banks (1983) found that sicklepod control was increased when the insecticide toxaphene was mixed with 2,4-DB or acifluorfen. The activity of bentazon was also increased when applied in combination with the insecticides malathion, parathion, and diazinon, either as a mixture, or 3 or 48 h apart (Campbell and Penner 1982).…”
Section: Introductionmentioning
confidence: 99%